Comprehensive Meta-Analysis of Attention-Deficit/Hyperactivity Disorder Psychosocial Treatments Investigated Within Between Group Studies. (October 2021) - Fabiano, Gregory A.; Schatz, Nicole K.; Aloe, Ariel M.; Pelham, William E.; Smyth, Alyssa C.; Zhao, Xin; Merrill, Brittany M.; Macphee, Fiona; Ramos, Marcela; Hong, Natalie; Altszuler, Amy; Ward, Leah; et al.
Interventions for attention-deficit/hyperactivity disorder (ADHD) include positive behavior supports (e.g., parent training, school-based contingency management, behavioral peer interventions), training interventions (e.g., organizational skills training, social skills training, etc.), and other interventions (e.g., academic accommodations/modifications, self-monitoring). There is a need to conduct a comprehensive meta-analysis of psychosocial treatments for ADHD given discrepancies between meta-analyses. The present meta-analysis reports the results of between-group studies that compared a psychosocial treatment to a control condition from 1968 to 2016. In total, 226 studies were identified that met inclusion criteria. Results of the meta-analysis were organized by treatment type, rater, and domain of outcome assessed. Results indicated considerable variability across these parameters, with the strongest effects for proximal outcomes of behavioral parent training (improvements in parenting behaviors yielded a standardized mean difference of 0.70) and improvements in child behavior following implementation of behavioral school intervention (standardized mean difference of 0.66 and 0.72 for teacher ratings of ADHD symptoms and impairment, respectively). Other interventions were not extensively studied as stand-alone approaches. Results are discussed in light of current support for the use of psychosocial interventions for individuals with ADHD.